Growth of Fruit Plants as Influenced by Nitrogen Fixing Bacteria - Rao, A V; Dass, H C (Annals of Arid Zone, 2016)
Inoculation of jujube (Ziziplzus mauritialla) and pomegranate (Pullica granatum) plants with nitrogen fixing bacteria enhanced the height and dry weight of plants as compared to the uninoculated control plants. There was a strain-variety interaction among the strains. A marked increase in the root biomass of these fruit plants upon inoculation with nitrogen fixing bacteria was also observed. Though there was no increase in the per cent N in the plants with inoculation. the total N-uptake was more with the inoculated plants. The rhizosphere of inoculated plants carried higher population of Azospirillum brasilellse as compared to the uninoculated control plants.